EVALUASI PENETAPAN FORMULASI KEBIJAKAN PAJAK HIBURAN DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA BATU - SYAHPUTRA, DIMAS WEIBY (Jurnal Mahasiswa Perpajakan, 2015)
This research aims to know the background of the Batu City Government in making policies entertainment. Tax rate is increasing in the Regional Regulation No. 6 of 2010 and decreased in the tax rate entertainment in Regional Regulation No. 2 of 2012 also analyzing the impact of the posed to the entertainment tax revenue in Batu. Another objective of this research is to determine the factors supporting and entertainment in the process of tax collection in Batu. The results of this study are revenues from entertainment tax Batu running optimally with the enactment of the Regional Regulation No. 2 of 2012 compared with the Regional Regulation No. 6 of 2010. The researchers also find a discrepancy between the formulation of the Government of Batu City with applicable laws, namely the absence of a Standard Operating Procedure (SOP) and an academic paper in the process of establishing local regulations on entertainment tax. Factors supporting the entertainment tax collection in Batu are the awareness of the taxpayer in paying taxes and a beautiful geographic of Batu. While the factors inhibiting the entertainment tax collection in Batu is presence of actors who commit fraud in the payment of taxes and infrastructure conditions Batu inadequate. Keywords: Policy Public Formulation, Entertainment Tax